Eucalyptus globulus biomass residues from pulping industry as a source of high value triterpenic compounds - Domingues, R. M. A.
The chemical composition of the lipophilic extracts of Eucalyptus globulus harvesting residues and bark generated by the pulp industry was studied by gas chromatography-mass spectrometry. Triterpenoids, mainly triterpenic acids with lupane, ursane and oleanane skeletons (namely, betulonic, betulinic, ursolic, oleanolic, 3-acetylursolic and 3-acetyloleanolic acids) were the major components detected. Triterpenoids contents range from 1.2 g/kg to 121.1 g/kg in fruits and surface layers of branches bark residues, respectively, being the triterpenic acids highly concentrated in surface layers of E. globulus biomass. The results demonstrate that these biomass residues can be considered as promising sources of valuable bioactive chemicals, opening new strategies to up-grade the pulp industry residues, within an integrated biorefinery context. The exploitation viability of the bark from an industrial pulp mill debarking process was evaluated. The recovery of triterpenoids from bark samples collected along the industrial debarking line decreases substantially, showing that a successful exploitation process of these valuable compounds in an integrated way will require the development of modifications on the debarking systems. (C) 2009 Elsevier B.V. All rights reserved.